RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN KENAIKAN JABATAN PEGAWAI DENGAN METODE PROFILE MATCHING (Studi Kasus: Kementerian Agama Kantor Wilayah DKI Jakarta) - Ernawati Ernawati; Nur Aeni Hidayah; Elvi Fetrina (UIN Syarif Hidayatullah Jakarta, 2017)
Ministry of Religious Affairs Jakarta Regional Office does not have a decision support system that can help the process of echelon structural rise. The structural position of echelon at the Regional Office of the Ministry of Religious Affairs of DKI Jakarta amounted to 41 people with details of 1 person occupying Echelon II, 10 people occupying the Echelon III, and 30 people occupying the Echelon IV. Basically the process undertaken for promotions begins with the announcement of vacancies, the selection of administrative and competence selection, until the results of the selection will be reported to the Chairman of the Baperjakat for trial. This raises the constraints in terms of time, the vacancy announced 2 weeks before the last limit of file collection is not enough considering not all employees read the information board. In addition to time, paper-based paperwork will cost 25 sheets of paper for each candidate that will eventually become a pile of paper by the end of the year and data searching becomes more difficult. The design of this decision support system uses the steps in SPK modeling which consists of feasibility study, designing, selecting, and making SPK. From this research, the result of the design of decision support system of employee promotion by using profile matching method at the Ministry of Religious Affairs of Jakarta Regional Office is expected to facilitate the provision of vacant vacancy information to be viewed by employees at any time through the website and minimize the amount of paper usage. After the SPK, no files have to be collected because the files can already be uploaded in the system. And the time required for reduction approximately 20 minutes before the system can occur approximately 2 days, so the efficiency level to 50%.